(4x-5)(5x+3)=

Simple and best practice solution for (4x-5)(5x+3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x-5)(5x+3)= equation:


Simplifying
(4x + -5)(5x + 3) = 0

Reorder the terms:
(-5 + 4x)(5x + 3) = 0

Reorder the terms:
(-5 + 4x)(3 + 5x) = 0

Multiply (-5 + 4x) * (3 + 5x)
(-5(3 + 5x) + 4x * (3 + 5x)) = 0
((3 * -5 + 5x * -5) + 4x * (3 + 5x)) = 0
((-15 + -25x) + 4x * (3 + 5x)) = 0
(-15 + -25x + (3 * 4x + 5x * 4x)) = 0
(-15 + -25x + (12x + 20x2)) = 0

Combine like terms: -25x + 12x = -13x
(-15 + -13x + 20x2) = 0

Solving
-15 + -13x + 20x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-3 + -5x)(5 + -4x) = 0

Subproblem 1

Set the factor '(-3 + -5x)' equal to zero and attempt to solve: Simplifying -3 + -5x = 0 Solving -3 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -5x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -5x = 0 + 3 -5x = 0 + 3 Combine like terms: 0 + 3 = 3 -5x = 3 Divide each side by '-5'. x = -0.6 Simplifying x = -0.6

Subproblem 2

Set the factor '(5 + -4x)' equal to zero and attempt to solve: Simplifying 5 + -4x = 0 Solving 5 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -4x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -4x = 0 + -5 -4x = 0 + -5 Combine like terms: 0 + -5 = -5 -4x = -5 Divide each side by '-4'. x = 1.25 Simplifying x = 1.25

Solution

x = {-0.6, 1.25}

See similar equations:

| 144-100y^2= | | (4x^3-7y^3)(4x^3+7y^3)= | | 5x^2+4x+1= | | y=(5x+3)(2x-1) | | (10x-5y)/(7y-14x) | | 3x+6y=93 | | 9/y-4 | | (1+xy)ydx+(1-xy)xdy=0 | | 5(2x+2)-3+8+3(2x+3)=7+2-3 | | a-(-2)= | | 15+15(_12)= | | 7(2x-3)+2(3x+3)=3-2+5 | | x^3+4x^2+31x-30=0 | | 3x+2y=285 | | (3x+1)(3x+1)(3x+1)(3x+1)= | | 3(7+2x)=5(2x+4x) | | 2x-3y=3x+8y | | -16+4x-7x=5-6x | | a-(b-(c+d))= | | 12p-(5+2p)= | | -6(5k+4)=-144 | | (2x-3)(2x-3)(2x-3)= | | 62x+44+2x=-20 | | (3x+y)(3x+y)(3x+y)= | | 2x-x-14=0 | | 125x^6+27y^3= | | (3*3*3*3)-79=2 | | 3x^2-79=2 | | (x-5)(x+8)=10 | | (2x^2+3)+(4x^3+1)= | | y=x^4tan(5x) | | (X+y)-6x+8y= |

Equations solver categories